Experimental evaluation of a transcritical CO2 refrigeration facility working with an internal heat exchanger and a thermoelectric subcooler: Performance assessment and comparative. (September 2022) - Casi, Álvaro; Aranguren, Patricia; Araiz, Miguel; Sanchez, Daniel; Cabello, Ramon; Astrain, David
Highlights: Solutions to boost the COP of low-medium power transcritical CO2 refrigeration cycles Evaluation of an internal heat exchanger (IHX) and a thermoelectric subcooler (TESC) Comparative of COP and cooling capacity between the IHX and the TESC Greater improvements obtained in the COP and cooling capacity with the TESC Discussion of the strengths and weaknesses of both technologies for transcritical CO2 Abstract: The use of carbon dioxide in transcritical state has become one of the most used solutions to comply with the F-Gas directive and reduce greenhouse gases emissions from refrigeration systems at high ambient temperatures. For low-medium power units, the commonly used solutions to improve the efficiency such as the ejector, multiple compressor arrangements, mechanical subcooler, etc., add complexity and increase the cost of the refrigeration facility, which is not ideal for small units. In this low-medium power range, two technologies stand out to increase the performance of a carbon dioxide transcritical cycle: the internal heat exchanger and the thermoelectric subcooler. This study brings a complete research in which both solutions have been tested in the same experimental transcritical carbon dioxide refrigeration facility under the same working conditions. It focuses on the real performance of both systems and discusses the strengths and weaknesses of using an internal heat exchanger or a thermoelectric subcooler. The results show that the thermoelectric subcooler outperforms the internal heat exchanger in both the coefficient of performance and the cooling capacity while also being a more controllable and flexible solution.